Frequency of Thrombocytopenia in Admitted Patients with Sepsis (Medical Forum Monthly, 2022)
Objective: Low platelet level is commonly seen in patients who are admitted with sepsis. It is one of the sequential hematological events that can lead to organ dysfunction and organ failure. The objective of the study was to look into frequency of thrombocytopenia in septic patients and its association with Diabetes, Hypertension and Obesity.Study Design: Prospective cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of medicine, Ayub Teaching Hospital Abbottabad. The study was carried out from 10th February 2021 to 09th January 2022.Materials and Methods: Total of 94 patients who were admitted into Ayub Teaching Hospital with sepsis were included in the study applying the inclusion and exclusion criteria.Results: Of these 94 cases, 49 (52.1 %) were male while 45 (47.8 %) were female patients. The mean age was 51.48 ± 10.25 years (with the minimum age of being 32 years while the maximum 76 years). 41 (64.0%) belonged to rural areas and 53 (56.3%) to urban areas. economically, 44 (46.8%) poor, and 50 (53.1%) belonged to the middle-income category. Diabetes was present in 33 (35.1 %) and hypertension 55 (58.5 %). The mean body mass index was 26.11 ± 1.75 kg/m2 and obesity was present in 20 (21.2 %). The mean platelet count was 153576.23 ± 87752.57 / microliter and thrombocytopenia were noted in 49(52.1%) cases.Conclusion: Low platelet count was seen in significant number of patients in our study with sepsis. It was also seen in this study that patients with Diabetes Mellitus, Hypertension and obesity were mainly associated with low platelets. It is recommended to correct timely blood glucose and Blood pressure. Similarly avoiding obesity can improve the outcome.